The New Strategy of the U.S. Middle East Policy and Egypt - Gevorgyan, Gor (ՀՀ ԳԱԱ Արևելագիտության ինստիտուտ)
After the collapse of the USSR, the United States further activated its policy in different continents with the aim of replenishing the so-called “vacuum space” that had resulted from the collapse of the bipolar system. In the light of formation of new correlation of world forces, the American foreign policy focused mostly on those parts of the world that were of direct importance to US national security.
Keywords: Political science